EVALUATION OF OPERATION PATTERNS AT THE AJIBATA-TOMOK PORT NORTH SUMATERA PROVINCE - Sari, Yulia Puspita; Khairani, Muhammad; Komalasari, Yeti; Atika, Aulia Ika; Fatista, Elga (IWTJ : International Water Transport Journal, 2024)
On the Ajibata-Tomok route, there are still vehicles and passengers that are not loaded onto the ship, so that service users must wait for the next departure. This can certainly be detrimental to service users, for example for service users who bring vehicles containing logistics for Samosir Island, where if there is a delay it can disrupt the economic activities of Samosir Island. Therefore, this study aims to determine the ship load factor, efficient operating patterns and departure schedule planning based on the number of ship trips. This study is quantitative with a calculation formulation that is analyzed using several load factor analysis methods, passenger and vehicle growth prediction analysis using the arima method, ship frequency analysis, and scheduling analysis. Based on the analysis results, the departure load factor on the Ajibata-Tomok route for passengers is 30% and vehicles is 95%, lay over time is 48.58 minutes, and the current ship round trip time is 203.96 minutes. The frequency of the existing fleet is 2 ships with 12 trip departures/day, making the ship schedule serving the Ajibata-Tomok route still inappropriate. So a scheduling plan is designed according to the needs of service users, namely 5 trips/ship/day and an additional ship fleet is needed to become 3 ships. The results of passenger and vehicle growth forecasts show that productivity will continue to increase by 44% each year. Planning an efficient ship departure operating pattern can reduce the ship load factor.